Lineament mapping in a tropical environment using Landsat imagery - Ramli, Mohammad Firuz; Tripathi, Nitin Kumar; Yusof, Norhakim; Mohd Shafri, Helmi Zulhaidi; Ali Rahman, Zulfahmi (Taylor & Francis, 2009)
Remote sensing has proved to be a useful tool in lineament identification and mapping. This study demonstrates the use of multispectral Landsat Thematic Mapper (TM) and Enhanced Thematic Mapper Plus (ETM +) satellite data obtained over two acquisition dates in 1990 and 2002 for lineament interpretation in a Malaysian tropical environment. A digital elevation model (DEM) was generated to improve the interpretation. We found that most of the major orientations in the field station could be successfully detected from the remotely sensed imagery. The results from the study show that the remote sensing technique is capable of extracting lineament trends in an inaccessible tropical forest.